An Island of Multiple Bridges : HISK laureates 2019 Exhibition. - Géo, Daniella (Ghent : HISK, 2019)
Caesar, Sofia ; de Greeuw, Lisette ; Ferreri, Francesca ; Giolo, Eva ; Hansen, Johna ; Heilig, Megan-Leigh ; Hensel, Sina ; Heremans, Roel ; Klück, Mirthe ; Mevis, Hannah ; Pozlep, mark ; Sánchez Barroso, Bárbara ; Skvernyte, Gintaute ; Vaikla, Ingel
HISK Laureats exhibition 2019 An Island of Multiple Bridges, Ghent, november 2th to december 15th 2019
boek